Novel Co-Processed Superdisintegrants in the Design of Fast Dissolving Tablets - S.B.Shirsand; R. G. Ramani; P.V.Swamy (International Journal of Pharma and Bio Sciences, 2010)
In the present study, novel co-processed superdisintegrants were developed by solvent evaporation method using crospovidone and sodium starch glycolate in different ratios (1:1, 1:2 & 1:3) for use in the fast dissolving tablet formulations. The developed excipients were evaluated for angle of repose, Carr’s index and Hausner’s ratio in comparison with physical mixture of superdisintegrants. The angle of repose of the developed excipients was found to be < 25o, Carr’s index in the range of 10-15% and Hausner’s ratio in the range of 1.13-1.16. Fast dissolving tablets of metoclopramide hydrochloride were prepared using the above co-processed superdisintegrants and evaluated for pre-compression and post-compression parameters. Based on in vitro dispersion time (approximately 19 sec), promising formulation CP1 was tested for in vitro drug release pattern in pH 6.8 Phosphate buffer, short-term stability (at 400C/75% RH for 3 months) and drug excipient interaction (IR spectroscopy). Among the designed formulations, the formulation (CP1) containing 4% w/w of co-processed superdisintegrant (1:1 mixture of crospovidone and sodium starch glycolate) emerged as the overall best formulation (t50% 1.30 min) based on drug release characteristics in pH 6.8 phosphate buffer compared to commercial conventional tablet formulation (t50% 6 min). Short-term stability studies on promising formulation indicated that there were no significant changes in drug content and in vitro dispersion time (p<0.05).